Auto-inhibitory intramolecular S5/S6 interaction in the TRPV6 channel regulates breast cancer cell migration and invasion - Ruiqi Cai (Nature Portfolio, 2021)
Cai et al discover an auto-inhibitory interaction between the S5 and S6 helices in the calcium-selective channel TRPV6. Molecular dynamics simulations predict that pathogenic mutation R532Q in S5 results in channel gain-of-function, which is confirmed in breast cancer migration, invasion and apoptosis assays.